A Study on Bipolar Soft \(b\)-Metric Spaces - Dhawan, Pooja; Grewal, Akshu (Communications in Mathematics and Applications, 2025)
In this work, bipolar soft \(b\)-metric space is introduced, which is constructed from \(b\)-metric space and several soft point sets. Also, using this framework, several fixed point theorems illustrated using bipolar soft contractive mappings and offer significant clarifications on this idea through medical applications.
Keywords: b-Metric spaces; Contraction mappings; Bipolar soft metric spaces